Periodontitis: Modern Approaches to Treatment and Prevention. Clinical Results - Azimov Saidabror Kayumjon ugli (Zien Journals, 2025)
Periodontitis is one of the most common chronic inflammatory diseases of the periodontal tissues and is a leading cause of premature tooth loss in adults. The disease is characterized by a progressive course, a tendency to recur , and a close relationship with systemic pathology. This article presents modern approaches to the treatment and prevention of periodontitis and analyzes the clinical effectiveness of combination therapy. A clinical observation of patients with chronic periodontitis was conducted. In a study of patients with generalized periodontitis, the dynamics of clinical indicators and the sustainability of remission were assessed using preventive programs. The results demonstrate the high effectiveness of comprehensive treatment combined with systemic prevention and follow-up.
Keywords: Periodontitis; inflammatory periodontal diseases; treatment